WiFi Signal Strength Degradation Over Different Building Materials - Aileen Aileen; Alexander Dennis Suwardi; Fernando Prawiranata (Bina Nusantara University, 2021)
Wireless Fidelity (WiFi) signals experience propagation through air and material in a building. This propagation causes signal decreasing signal strength. This study aims to determine materials in buildings that cause significant signal strength loss so in the future building design could factor in signal strength by using material that doesn't affect signal strength significantly. The testing of signal strength will be done by observing signal strength through different materials. Signal strength will be recorded by using a mobile app. Materials that majorly decrease signal strength are plastics, with the least affecting materials are hollow plywood wall. The use of plastics in a building affects significantly on signal loss and should be replaced if possible with hollow plywood walls.